Pengaruh Variasi Konsentrasi Basis Beeswax Dan Paraffin Wax Pada Lip Balm Ekstrak Bunga Soka Merah (Ixora coccinea L.) - Setiyawati, Bayu; Endriyatno, Nur Cholis (Poltekkes Kemenkes Bengkulu, 2025)
Soka flower extract (Ixora coccinea L.) is a very powerful source of natural antioxidants. Soka flower extract is formulated as a lip balm to utilize its potential as an antioxidant that can protect the lips. This study aims to determine the effect of variations in the concentration of beeswax and paraffin wax bases on the physical properties of soka flower extract lip balm preparations and to obtain the best component variations. Soka flowers were extracted using maceration extraction using 96% ethanol. The lip balm preparations were made in 3 formulas with variations in the concentration of beeswax and paraffin wax bases, namely FI (5%:15%), FII (7.5%:12.5%), and FIII (10%:10%). The lip balm was evaluated for physical properties such as organoleptic tests, homogeneity tests, pH tests, spreadability tests, smearability tests, adhesion tests, irritation tests, and moisture tests. Data analysis was carried out using the One Way ANOVA method. Based on the results of the study, it was shown that variations in the concentration of beeswax and paraffin wax bases affected the physical properties of the preparations, including pH, adhesiveness, spreadability, and viscosity. In this study, FII (7.5% beeswax and 12.5% paraffin wax) was determined as the best formula for the soka flower extract lip balm preparation, based on consideration of the requirements and statistical tests.